Multidrug-resistant pathogens in patients with pneumonia coming from the community. Issue 3 (May 2016) - Sibila, Oriol; Rodrigo-Troyano, Ana; Shindo, Yuichiro; Aliberti, Stefano; Restrepo, Marcos I.
Abstract : Purpose of review: Identification of patients with multidrug-resistant (MDR) pathogens at initial diagnosis is essential for the appropriate selection of empiric treatment of patients with pneumonia coming from the community. The term Healthcare-Associated Pneumonia (HCAP) is controversial for this purpose. Our goal is to summarize and interpret the data addressing the association of MDR pathogens and community-onset pneumonia. Recent findings: Most recent clinical studies conclude that HCAP risk factor does not accurately identify resistant pathogens. Several risk factors related to MDR pathogens, including new ones that were not included in the original HCAP definition, have been described and different risk scores have been proposed. The present review focuses on the most recent literature assessing the importance of different risk factors for MDR pathogens in patients with pneumonia coming from the community. These included generally MDR risk factors, specific risk factors related to methicillin-resistant Staphylococcus aureus or Pseudomonas aeruginosa and clinical scoring systems develop to assess the MDR risk factors and its application in clinical practice. Summary: Different MDR risk factors and prediction scores have been recently developed. However, further research is needed in order to help clinicians in distinguishing between different MDR pathogens causing pneumonia.